AN ANALYSIS ON TEACHER’S COMMUNICATION STRATEGIES IN TEACHING SPEAKING AT MTS NW BONJERUK - Muhlisin, Muhammad; Widyanto, Anugrah (JOLLT Journal of Languages and Language Teaching, 2019)
The objectives of this study are to reveal what communication strategies used by an English teacher in communication with first-grade students of MTs NW Bonjeruk. The research used a qualitative approach, more specifically classroom discourse analysis in analyzing this study since the source of the data was communication strategies which are used by an English teacher in communicating with students during an English teaching-learning activity. The result of the study showed that there were four of five communication strategies proposed that appeared in the teaching-learning process. They were achievement or compensatory strategies, stalling or time gaining strategies, self-monitoring strategies, and interactional strategies. The strategy which was not found in the transcription is avoidance or reduction strategy. Based on the results of the study, the teacher often uses code-switching more than other strategies.